2006
DOI: 10.1111/j.1743-6109.2005.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oral Contraceptives on Sex Hormone-Binding Globulin and Androgen Levels: A Retrospective Study in Women with Sexual Dysfunction

Abstract: Introduction Oral contraceptives (OCs) have been the preferred method of birth control because of their high rate of effectiveness. OC use, however, has been associated with women's sexual health complaints and androgen insufficiency. OC use is associated with a decrease of androgen ovarian synthesis and an increase in the production of sex hormone-binding globulin (SHBG). There have been limited studies assessing SHBG values after discontinuation of OC use. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 40 publications
(62 reference statements)
7
83
1
2
Order By: Relevance
“…In this study, we showed that pregnant women and women using OAC have higher SHBG concentrations (6-and 2-fold, respectively). This confirms the results from previous studies, showing a 5-to 10-fold increase during pregnancy (13,14) and a 2-to 4-fold increase in women using OAC (15,16), which is due to estrogens stimulating the liver to produce SHBG. Increased serum SHBG concentrations are also seen in samples from patients with anorexia nervosa, hyperthyroidism, and Cushing disease (17).…”
supporting
confidence: 92%
“…In this study, we showed that pregnant women and women using OAC have higher SHBG concentrations (6-and 2-fold, respectively). This confirms the results from previous studies, showing a 5-to 10-fold increase during pregnancy (13,14) and a 2-to 4-fold increase in women using OAC (15,16), which is due to estrogens stimulating the liver to produce SHBG. Increased serum SHBG concentrations are also seen in samples from patients with anorexia nervosa, hyperthyroidism, and Cushing disease (17).…”
supporting
confidence: 92%
“…Detrimental effects of oral contraceptives on sexual functioning may be sustained after discontinuation of the medications. 37 However, removal of this variable from the final model with addition of the sexual frequency construct suggests this finding lacks robustness. There was no difference between current and never smokers in sexual satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even though several questionnaires contain items relating to partner-focused sexual satisfaction, which is likely correlated with desire, these items are often subsumed within global sexuality scores or in desire subscales which also incorporate general sexual desire (e.g., Panzer et al, 2006;Wallwiener et al, 2010).…”
Section: Defining the Object Of Desirementioning
confidence: 99%
“…It is perhaps remarkable that several studies fail to do this (e.g. Fortenberry & Hensel, 2011;Panzer et al, 2006). Even in those that do, including many who specifically recruit partnered women, few record changes in relationship status across the study.…”
Section: Future Directionsmentioning
confidence: 99%